2012
DOI: 10.1098/rspb.2012.0509
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the influence of parasite genotype, host genotype and maternal environment on different stages of bacterial infection in Daphnia magna

Abstract: Individuals naturally vary in the severity of infectious disease when exposed to a parasite. Dissecting this variation into genetic and environmental components can reveal whether or not this variation depends on the host genotype, parasite genotype or a range of environmental conditions. Complicating this task, however, is that the symptoms of disease result from the combined effect of a series of events, from the initial encounter between a host and parasite, through to the activation of the host immune syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 44 publications
(76 reference statements)
3
75
0
Order By: Relevance
“…Recent work has suggested that genetic variation in disease characteristics can vary considerably over the course of infection, potentially influencing the evolution of the parasite [9,11,18]. Here, we quantified parasite genetic variation for three key disease traits over the duration of an entire infection process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent work has suggested that genetic variation in disease characteristics can vary considerably over the course of infection, potentially influencing the evolution of the parasite [9,11,18]. Here, we quantified parasite genetic variation for three key disease traits over the duration of an entire infection process.…”
Section: Discussionmentioning
confidence: 99%
“…the degree of differences among parasite genotypes) of virulence and transmission changes with the age of the infection, raising the question whether such within-host dynamics matter for the evolution of the parasite and thus for disease traits? Ultimately, the consequences of any within-host patterns for evolutionary dynamics depend on a direct link to parasite transmission success [9,11,18]. A lack of variability (and evolutionary potential) early in the infection process would be irrelevant if all infected animals were able to progress through to the end of the infection process, when the parasite induces host death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Steps of the infection process P. ramosa's infection process can be subdivided into a number of steps: encounter, spore activation, attachment, penetration of the host cuticle and within-host steps (Duneau et al, 2011;Hall and Ebert, 2012). The host's interference with any of these steps could contribute to host resistance.…”
Section: Fine Mapping Of Resistance Genesmentioning
confidence: 99%